Impact of FOMWAN in Bauchi State of Nigeria, 2007-2013 - Gar, Ruqayya Aminu (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
The Federation of Muslim Women Association in Nigeria (FOMWAN) is one of the non-governmental organizations with a specific focus on women issues in Nigeria. Currently, no research has been carried out to assess the impact of women empowerment programs in Bauchi state by FOMWAN particularly on the targeted beneficiaries. Therefore, this study attempts to examine the impact of FOMWAN's Women empowerment programmes in Bauchi and assess to what extent they empower women in Bauchi. Furthermore, it also examines the strategies employed in selecting the target beneficiaries and the challenges faced by the association. This study is a quantitative one which utilized questionnaires to collect data from both the beneficiaries of the association's programmes as well as from FOMWAN officials. A sample size of 300 was used out of the 4000 research population and a 5- point likert scale was used in the questionnaire. The Statistical Package for Social Science 20th edition (SPSS) was used to analyse the collected data. Findings of the study indicated that FOMWAN uses informational, moral and economic resources adequately to empower women and that the women beneficiaries are selected via town hall meetings, seminars, workshop and sensitization and awareness campaigns with the help of community and religious leaders. Despite the success recorded, the association faces some challenges including insufficient funding, inadequate resource management and inadequate administrative skills among its employees